Methods Related to Herbicide Dissipation or Degradation under Field or Laboratory Conditions. Issue Volume 63: Issue SP1(2015) (February 2015) - Mueller, Thomas C.; Senseman, Scott A.
Abstract : Herbicide degradation in soil is a major research issue, as evidenced by the number of refereed articles on the subject (Figure 1). The approximate number of total citations per year has increased from about 70 in the mid-1990s to approximately 170 per year in the last few years (Figure 1a). From a weed science perspective, publications in the journals Weed Science and Weed Technology have tended to decline from an average of eight per year in the 1995 to 2005 interval to about three per year in the last 10 yr (Figure 1b). This discrepancy of total citations vs. Weed Science Society of America journals may be due to funding availability and other more immediate research needs in weed science. Other reasons might be a lack of reader interest (indicating low potential impact in this specific topic area) or the perception that Weed Science and Weed Technology are light venues for such papers and therefore not the first choice for publication. The authors believe this research topic to be important and relevant to the discipline of weed science, even more so as herbicide use patterns become more complicated because of glyphosate-resistant (GR) weeds.